Comparison of fluorene, silafluorene and carbazole as linkers in perylene monoimide based non-fullerene acceptors. Issue 6 (3rd September 2020) - Weber, Stefan; Hofinger, Jakob; Rath, Thomas; Reinfelds, Matiss; Pfeifer, David; Borisov, Sergey M.; Fürk, Peter; Amenitsch, Heinz; Scharber, Markus C.; Trimmel, Gregor
Abstract : Perylene monoimide based non-fullerene acceptors with fluorene, silafluorene and carbazole as linkers were synthesized and compared regarding their structural, optical, electronic and photovoltaic properties. Abstract : Perylene monoimide (PMI ) based non-fullerene acceptors are an interesting alternative to perylene diimide acceptors in organic photovoltaics due to an open substitution side allowing chemical modifications of the molecule. In addition, this offers the possibility to twist the molecule to avoid pronounced π–π stacking. At the same time, the good solubility and the well-suited optical properties are maintained. This work provides a new perspective of perylenes using PMI -linker-PMI based acceptors in which the linker is composed of different fluorene derivatives to investigate the influence of heteroatoms on the optical and electronic properties. The three compounds PMI-F-PMI, PMI-FSi-PMI and PMI-FN-PMI were synthesized using a fluorene (F), silafluorene (FSi) and carbazole (FN) linker, respectively, characterized regarding optical, structural and electronic properties and implemented in solar cells using PBDB-T as donor material. The influence of the donor/acceptor ratio as well as thermal annealing on the solar cell properties were studied and maximum device efficiencies of 5.16% and high photovoltages up to 1.14 V were obtained for all three acceptors. Moreover, the solar cells display reasonable stability in inert conditions as is exemplified by maximum power point tracking experiments under continuous illumination.